The policy of strategic demobilisation: the social policy of the Christian Democratic-Liberal coalition, 2009-13 - Schmidt, Manfred G. (German politics, 2014)
This article addresses two research questions: which course did the CDU, CSU-FDP coalition government choose to follow in social policy from 2009 to 2013? And what relationships exist between social policy in this period and the Bundestag election in 2013? The analysis of primary and secondary data reveals both continuity and discontinuity in social policy in the 17th legislative period of the Bundestag. The decisions and non-decisions on social protection and labour market regulation in this period mirror a wide variety of determinants. These include partisan effects, electoral cycles, co-governing judges and anonymous social policy of market forces. The data also suggest that the CDU/CSU has been relatively successful in its strategy of ‘asymmetric demobilisation’, the strategy of changing its social policy profile to one more similar to that of its social democratic opponent, in order to demobilise the SPD's voters rather than mobilising them. More ambivalent has been the electoral outcome of the FDP's role in social policy. The FDP's first foray into leading a large welfare state ministry, the Federal Ministry of Health, in 2009 to 2013 did not prove to be a winning proposition for the Liberals electorally. Social policy in general and welfare state recalibration in particular thus seem to be an electorally especially risky project for a liberal party such as the FDP.